Appropriate therapy for patients with stable ischemic heart disease: a review of literature and the implication of the International Study of Comparative Effectiveness with Medical and Invasive Approaches trial. (November 2020) - Guo, Ming Hao; Nantsios, Alex; Ruel, Marc
Abstract : Purpose of review: The aim of this review is to review the current literature on the management of stable ischemic heart disease in light of findings from the International Study of Comparative Effectiveness with Medical and Invasive Approaches (ISCHEMIA) trial. Recent findings: Compared with optimal medical therapy, coronary artery bypass grafting (CABG) has been shown to improve survival and incidence of myocardial infarction in patients with stable ischemic heart disease whereas percutaneous coronary intervention (PCI) has not. The ISCHEMIA trial compared an initial conservative management strategy with optimal medical therapy with an initial invasive strategy with coronary angiogram followed by revascularization and found no difference in survival and myocardial infarction between the two groups. However, the trial was conducted under the assumption that patients would be referred to the most efficacious revascularization therapy; it was apparent that CABG was underutilized in many appropriate patients in the ISCHEMIA trial. The study highlighted the importance of optimizing medical therapy in stable ischemic heart disease (SIHD) patients but does not answer whether revascularization or conservative management is better for patients with SIHD. Summary: Optimal medical therapy is an important element and should be included in the Heart Team discussion, and also applied after revascularization from PCI or CABG. Cardiac surgeons need to continue to advocate for the appropriate use of CABG based on the current available evidence.